2007
DOI: 10.1002/anie.200702519
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Nanostructured Arrays of Sodium Rare‐Earth Fluorides for Highly Efficient Multicolor Upconversion Luminescence

Abstract: Upconversion (UC) phosphors emit high-energy photons when they are excited by low-energy photons. This property is attractive for flat-panel displays, [1,2] optical storage, [3] biolabels, [4] solid-state lasers, [5] and light-emitting diodes.[6] High UC luminescence efficiency is typically generated by bulk materials [1] and colloidal nanocrystals [7] of hexagonal-phase lanthanide-doped rare-earth fluorides, but nanoarrays of single crystals are more desirable for solid-state lasers. The UC luminescence effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
213
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 351 publications
(223 citation statements)
references
References 17 publications
8
213
2
Order By: Relevance
“…[69] The mechanism of synthesizing different shapes of rare-earth fluoride nano-and microcrystals by using the hydrothermal method has been well described by Nie et al [70] Another interesting development was reported by Zhao and co-workers, [71] who utilized an oleic acid mediated hydrothermal method for the synthesis of upconverted NaYF 4 nanorods, nanotubes, and flower-patterned nanodisks. Li et al [72] reported the successful hydrothermal synthesis of high-quality monodisperse CaF 2 :Yb 3 + ,Er 3 + nanocrystals about 10 nm in size in a water/ethanol solvent mixture.…”
Section: Synthesis Of Rare-earth-doped Upconverted Nanocrystalsmentioning
confidence: 98%
“…[69] The mechanism of synthesizing different shapes of rare-earth fluoride nano-and microcrystals by using the hydrothermal method has been well described by Nie et al [70] Another interesting development was reported by Zhao and co-workers, [71] who utilized an oleic acid mediated hydrothermal method for the synthesis of upconverted NaYF 4 nanorods, nanotubes, and flower-patterned nanodisks. Li et al [72] reported the successful hydrothermal synthesis of high-quality monodisperse CaF 2 :Yb 3 + ,Er 3 + nanocrystals about 10 nm in size in a water/ethanol solvent mixture.…”
Section: Synthesis Of Rare-earth-doped Upconverted Nanocrystalsmentioning
confidence: 98%
“…Subsequent energy transfer from a sensitizer ion to the already excited activator ion produces new, higher energy states that can undergo emission as the result of 'upconversion'. The resulting emission (or emissions), which is the consequence of sequential multi-photon processes, occurs at a higher energy than the initial excitation source, as illustrated in figure 5 for a system with Yb 3+ as the sensitizer ion and Er 3+ as the activator ion [79]. With ETU, energy transfers to neighbouring ions are often between states that are not exact matches; that is, the transition involves excess or insufficient energy mismatch as illustrated in figure 6 [80].…”
Section: Uncaging Using Upconversion Nanoparticles (A) Introduction Tmentioning
confidence: 99%
“…Zhang et al had fabricated the upconversion rare-earth fluoride arrays by induced ␣-NaYF 4 :Yb 3+ /Er 3+ nanocrystals self-assembly inside the voids of a self-organized PS template via the MIMIC method, and demonstrated that the UC photoluminescence can be modified [9]. The ordered short-range rare earth fluoride nanoarrays synthesized by hydrothermal methods showed the highly efficient multicolor upconversion luminescence [7]. Ordered mesostructured LaF 3 nanoarrays have been synthesized via a one-step nanocasting process using La(CF 3 COO) 3 as a precursor and mesoporous silica as a hard template [10].…”
Section: Introductionmentioning
confidence: 96%
“…Recently, upconversion (UC) luminescent arrays selfassemblied by low-dimensional nanomaterial have attracted considerable attention due to their potential applications in flat-panel displays, optical storage, biolabels, solid-state lasers, and light-emitting diodes [1][2][3][4][5][6][7]. The UC luminescence efficiency can be enhanced if the nanoarrays are aligned with photoniccrystal microstructures, and the faceted end planes of well-shaped crystals serve as good laser-cavity mirrors [8].…”
Section: Introductionmentioning
confidence: 99%